The best of reporter's notebook - GMA News & Public Affairs (Manila GMA News & Public Affairs, 2008)
Collection of best episodes of Reporter's notebook, an investigative news magazine television show in the Philippines aired every Tuesday night by GMA Network.
Batang kalakal (13 min., 10 sec.) -- Pinoy Exodus sa Lebanon (18 min., 45 sec.) -- Backdoor (14 min.) -- Gatilyo (21 min., 07 sec.) -- Isla Fuga (23 min., 49 sec.)
Library has: VDR-1520 (1 DVD)
With bonus features.
Hosts, Malou Mangahas, Jiggy Manicad.
DVD
In Tagalog, with English subtitles.
Keywords: Nonfiction television programs; Documentary television programs